1999
DOI: 10.1007/bf02946475
|View full text |Cite
|
Sign up to set email alerts
|

Occupational noise levels in orthopaedic surgery

Abstract: Prolonged exposure to potentially damaging noise levels in the workplace has been the subject of much recent litigation. The occupational risk of noise induced hearing loss among orthopaedic surgeons is unknown. Continuous readings of air-powered instruments routinely used in orthopaedic surgery were made in a regional trauma unit at standard distance from the noise source. All instruments generated noise levels greater than the threshold for routine monitoring of hearing loss under health and safety legislati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…8 A separate study across 10 different surgeries found noise levels ranging from 71 dBA to 95 dBA during use of drills for orthopedic surgeries. [10][11][12] Surgical procedures in which these instruments are used, such as craniotomies and orthopedic surgeries, can last many hours, potentially exposing surgical staff members to long periods of noise. 9 Several other noise researchers have found noise levels during the use of surgical instruments (eg, drills, saws) exceeding 90 dBA.…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…8 A separate study across 10 different surgeries found noise levels ranging from 71 dBA to 95 dBA during use of drills for orthopedic surgeries. [10][11][12] Surgical procedures in which these instruments are used, such as craniotomies and orthopedic surgeries, can last many hours, potentially exposing surgical staff members to long periods of noise. 9 Several other noise researchers have found noise levels during the use of surgical instruments (eg, drills, saws) exceeding 90 dBA.…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…Within healthcare settings, high environmental noise in hospitals may be responsible for abnormal hearing among healthcare workers, 3,4 while the orthopaedic staff experienced the highest prevalence of hearing-associated problems, due to highpowered tools in orthopaedic theatres. [5][6][7][8][9][10] In the 1960s, environmental noise produced in dental healthcare settings was considered responsible for HI in the dental staff. [11][12][13] However in almost all previous studies dentists did not experience higher HI risk than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…͑A recent paper by Busch-Vishniac et al 3 presents an extensive review of the hospital noise literature.͒ Within hospitals, there is growing concern about noise in the operating theaters, but the literature on this topic is generally thin and often conflicting. The literature varies from editorials railing against noise in the operating room ͑OR͒ 4,5 to studies of the noise produced by tools used primarily in orthopedic surgery [6][7][8] and to reports of the sound pressure levels produced by a particular surgery. While rare, there are also a few reports of the effects of OR noise on performance and hearing.…”
Section: Introductionmentioning
confidence: 99%